Adherence to Antihypertensive Medication: An Interview Analysis of Southwest Ugandan Patients’ Perspectives - Najjuma, Josephine Nambi; Brennaman, Laura; Nabirye, Rose C.; Ssedyabane, Frank; Maling, Samuel; Bajunirwe, Francis; Muhindo, Rose (Annals of Global Health, 2020)
Hypertension is a significant cardiovascular disease (CVD) and driver to CVD disorders in sub-Saharan Africa. It is a major independent risk factor for heart failure, stroke, and kidney failure. Persons living with hypertension attend to many aspects of self-care to manage their condition, including high blood pressure medication adherence to control of blood pressure. Rates of medication non-adherence, and thus uncontrolled hypertension, remain high and contribute to poor health outcomes. Understanding barriers and facilitators to adherence to hypertension therapies can help improve health outcomes.The aim of the study was to describe the common reasons for adherence and non-adherence to antihypertensive medication from patients’ perspectives.A qualitative study engaged clients of an out-patient clinic of a regional referral hospital in southwestern Uganda who were living with hypertension as participants. One-on-one in-depth interviews provided the narrative data. The interview transcripts were analyzed using thematic analysis.Sixteen participants provided the data for the findings. The themes identified as facilitators for adherence to antihypertensive medication were patients’ understanding of prescribed medication, availability of medication for hypertension, family support for patients living with hypertension, and regular review appointments at the hypertensive clinics. Conversely, lack of supply in government dispensaries, use of self-prescribed analgesic medication, and stigma were identified as barriers and challenges of adherence to antihypertensive medication.There is an urgent need for the health ministry to improve availability of high blood pressure medication and for health care providers to deliver individualized patient centered care, and sensitization on danger of self-prescription and measures that reduce stigma. These strategies may improve adherence to high blood pressure medication.